The Influence of Algorithm Transparency, Trust, Price Perception, Service Quality, and Ease of Use on Marketplace Consumer Loyalty. - Nurul Aini; Khairul Umam (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of algorithm transparency, trust, price perception, service quality, and ease of use on the loyalty of marketplace consumers in Sumenep Regency. A non-probability sampling technique was employed, with data collected via Google Forms from 200 active users of major marketplaces—such as Shopee, TikTok Shop, and Lazada—residing in Sumenep Regency. Data analysis was conducted using SPSS. The results indicate that algorithm transparency, trust, price perception, service quality, and ease of use have a positive and significant impact—both individually and simultaneously—on marketplace consumer loyalty in Sumenep Regency.